Implementation of Child-Friendly School Programs in Shaping Disciplined Character - Salindry, Agesta Eka; Yuniar, Yuniar; Afriantoni, Afriantoni (Journal of English Language and Education, 2025)
This research focuses on the implementation of child-friendly schools. This study aims to explain: 1) The implementation of child-friendly schools 2) Efforts to form the character of student discipline through child-friendly school education; and 3) Supporting and inhibiting factors in the process of implementing child-friendly schools. This research is a qualitative descriptive type. Observation, interviews, and documentation are the methods used to obtain data. The data analysis used in this study was carried out by reducing data, which was then presented in descriptive form, and verified by drawing conclusions. The results of the study show that child-friendly schools that implement child-friendly school policies have a system that is free from violence and discrimination. The implementation of the curriculum which is used in accordance with the development of children, qualified educators and educators who have teacher qualifications. Adequate school facilities and infrastructure. Child participation where the teacher always involves the child in everything they do. Child-friendly school programs depend on the participation of parents and the community. All teachers' efforts to ensure that students come to school and enter on time, perform assigned classwork, sit in designated places, adhere to school and classroom rules to demonstrate orderly behavior, and dress neatly are part of the responsibility and discipline of students in school. The factors that support the implementation of Child-Friendly Schools are positive attitudes and support from various parties, which facilitate as much as possible the facilities and infrastructure for school needs.